Interobserver variability in the classification of appendicitis during laparoscopy. Issue 8 (16th April 2018) - van den Boom, A. L.; de Wijkerslooth, E. M. L.; Mauff, K. A. L.; Dawson, I.; van Rossem, C. C.; Toorenvliet, B. R.; Wijnhoven, B. P. L.
Abstract : Background: The intraoperative classification of appendicitis dictates the patient's postoperative management. Prolonged antibiotic prophylaxis is recommended for complex appendicitis (gangrenous, perforated, abscess), whereas preoperative prophylaxis suffices for simple appendicitis. Distinguishing these two conditions can be challenging. The aim of this study was to assess interobserver variability in the classification of appendicitis during laparoscopy. Methods: Short video recordings taken during laparoscopy for suspected appendicitis were shown to surgeons and surgical residents. They were asked to: classify the appendix as indicative of no, simple or complex appendicitis; categorize the appendix as normal, phlegmonous, gangrenous, perforated and/or abscess; and decide whether they would prescribe postoperative antibiotics. Inter‐rater reliability was evaluated using Fleiss' κ score and the S* statistic. Results: Some 80 assessors participated in the study. Video recordings of 20 patients were used. Interobserver agreement was minimal for both the classification of appendicitis (κ score 0·398, 95 per cent c.i. 0·385 to 0·410) and the decision to prescribe postoperative antibiotic treatment (κ score 0·378, 0·362 to 0·393). Agreement was slightly higher when published criteria were applied (κ score 0·552, 0·537 to 0·568). Conclusion: There is considerable variability in the intraoperative classification of appendicitis and the decision to prescribe postoperative antibiotic treatment. Abstract : Considerable